2017
DOI: 10.1371/journal.pone.0183014
|View full text |Cite
|
Sign up to set email alerts
|

Needs and concerns of transgender individuals regarding interdisciplinary transgender healthcare: A non-clinical online survey

Abstract: This study investigates the needs and concerns transgender (short: trans) individuals have concerning trans healthcare (THC) in interdisciplinary THC centres. Trans individuals’ gender does not (fully/constantly) match their sex assigned at birth. To be able to live in their gender role and to prevent or minimise gender dysphoria, they might require a multidisciplinary set of transition related healthcare services. The current shift from the traditionally highly regulated, hierarchical and pathologising approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
121
1
28

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(161 citation statements)
references
References 54 publications
(96 reference statements)
7
121
1
28
Order By: Relevance
“…Best practice TGD health services should be community-led and co-designed with the TGD community [4]. Previous small surveys have suggested that increased education of medical practitioners was needed to better engage with gender diverse clients [5].…”
Section: Introductionmentioning
confidence: 99%
“…Best practice TGD health services should be community-led and co-designed with the TGD community [4]. Previous small surveys have suggested that increased education of medical practitioners was needed to better engage with gender diverse clients [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is the first and so far only ITHC in Germany. It maintains close links with other ITHCs internationally (Kreukels et al, ) as well as with local trans healthcare stakeholders (Eyssel et al, ), thereby complying with EU and German Alliance for Rare Diseases standards (NAMSE, ; Winten & Werner, ). The ITHC in Hamburg takes a client‐centred approach to trans healthcare (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…For example online survey and community data show that expectations of rejection, self‐stigmatisation and discrimination are associated with distress (Timmins, Rimes, & Rahman, ), and that discrimination experiences related to identity, transition and disclosure of trans status are associated with a delayed accessing of healthcare (Cruz, ; Loos, Köhler, Eyssel, & Nieder, ). In order to minimise or prevent gender dysphoria, and to make living according to their gender possible or easier, trans individuals may access various transition‐related healthcare services, for example hormone treatment and surgeries (Murad et al, ; White Hughto & Reisner, ), which ideally work in close, interdisciplinary settings (Eyssel, Koehler, Dekker, Sehner, & Nieder, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations